A Comprehensive Analysis of Honor Killing Practices in Pakistan: Contributing Factors, Legal Frameworks, and Intervention Strategies - Muhammad Wasim Jan, Sahibzada (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2025)
Research Objective: This study examines women’s rights and honor killings in Pakistan, with particular attention to the socio-cultural and economic factors driving gender-based violence, especially the Karo-Kari practice in Sindhi culture. Research Method: The research employed a qualitative approach, drawing on a literature review and secondary data sourced from academic journals, legal documents, news reports, and human rights organizations, including Human Rights Watch and Amnesty International. Purposive sampling and thematic analysis were applied, with data triangulation employed to enhance accuracy and credibility. Results: The findings reveal interconnected drivers of honor killings, including patriarchal family systems, arranged marriages, property disputes, limited access to education, misinterpretations of religion, poverty, rigid social norms, and weak law enforcement. Findings and Implications: Honor killings are rooted in both cultural and economic motives, particularly the consolidation of property. Inadequate education perpetuates distorted religious justifications, while entrenched gender subordination fosters ideologies that normalize violence. Although legal reforms, such as the 2016 Act removing the option of family forgiveness, represent progress, enforcement remains ineffective due to corruption and inadequate investigations. Conclusion: Honor killings constitute a multifaceted problem that requires comprehensive interventions addressing cultural, economic, educational, and institutional dimensions simultaneously. Effective prevention demands coordinated efforts involving legal reform, educational initiatives, economic empowerment, and cultural transformation programs. Contribution: This study links historical legal reforms to contemporary patterns of honor-based violence, illustrating the relationship between economic hardship and gender-based violence while underscoring the role of NGOs in prevention. Limitations and Suggestions: As the study is based solely on secondary data, future research should incorporate interviews with survivors, families, and community leaders. Longitudinal studies assessing the effectiveness of interventions, as well as comparative analyses across different Pakistani provinces, could enhance understanding and support the development of more effective prevention strategies